New insights into US flood vulnerability revealed from flood insurance big data - Oliver E. J. Wing (Nature Portfolio, 2020)
Economic estimates of flood damages rely on depth–damage functions that are inadequately verified. Here, the authors assessed flood vulnerability in the US and found that current depth–damage functions consist of disparate relationships that match poorly with observations which better follow a bimodal beta distribution.